Response Modification Factor of RC Frames Strengthened with RC Haunches - Junaid Akbar; Naveed Ahmad; Muhammad Rizwan; Sairash Javed; Bashir Alam (Shock and Vibration)
This paper presents experimental and numerical studies carried out on two-story reinforced concrete (RC) frames having weaker beam-column joints, which were retrofitted with reinforced concrete haunches to avoid joint panel damage under seismic actions. The design philosophy of the retrofit solution is to allow beam-column members to deform inelastically and dissipate seismic energy. Shake table tests were performed on three 1 : 3 reduced scale two-story RC frame models, including one model incorporating construction deficiencies common in developing countries, which was retrofitted with two retrofit schemes using RC haunches. The focus of the experimental study was to understand the seismic behaviour of both as-built and retrofitted models and obtain the seismic response properties, i.e., lateral force-displacement capacity curves and time histories of model response displacement. The derived capacity curves were used to quantify overstrength and ductility factors of both as-built and retrofitted frames. Finite element- (FE-) based software SeismoStruct was used to develop representative numerical models, which were calibrated with the experimental data in simulating the time history response of structure roof displacement and in predicting peak roof-displacement and peak base shear force. Moreover, the FE-based numerical models were subjected to a suite of spectrum natural accelerograms, linearly scaled to multiple intensity levels for performing incremental dynamic analysis. Lateral force-displacement capacity and response curves were developed, which were analyzed to calculate the structure ductility and overstrength factors. The structure R factor is the product of ductility and overstrength factors, which exhibited substantial increase due to the proposed retrofitting technique. A case study was presented for the seismic performance assessment of RC frames with/without RC haunches in various seismic zones using the static force procedure given in seismic code and using response modification factor quantified in the present research.